Preventive Intervention for Living Donor Psychosocial Outcomes: Feasibility and Efficacy in a Randomized Controlled Trial - Dew, M. A.; DiMartini, A. F.; DeVito Dabbs, A. J.; Zuckoff, A.; Tan, H. P.; McNulty, M. L.; Switzer, G. E.; Fox, K. R.; Greenhouse, J. B.; Humar, A. (American journal of transplantation, 2013)
There are no evidence‐based interventions to prevent adverse psychosocial consequences after living donation. We conducted a single‐site randomized controlled trial to examine the postdonation impact of a preventive intervention utilizing motivational interviewing (MI) to target a major risk factor for poor psychosocial outcomes, residual ambivalence (i.e. lingering hesitation and uncertainty) about donating. Of 184 prospective kidney or liver donors, 131 screened positive for ambivalence; 113 were randomized to (a) the MI intervention, (b) an active comparison condition (health education) or (c) standard care only before donation. Ambivalence was reassessed postintervention (before donation). Primary trial outcomes—psychosocial variables in somatic, psychological and family interpersonal relationship domains—were assessed at 6 weeks and 3 months postdonation. MI subjects showed the greatest decline in ambivalence (p = 0.050). On somatic outcomes, by 3 months postdonation MI subjects reported fewer physical symptoms (p = 0.038), lower rates of fatigue (p = 0.021) and pain (p = 0.016), shorter recovery times (p = 0.041) and fewer unexpected medical problems (p = 0.023). Among psychological and interpersonal outcomes, they had a lower rate of anxiety symptoms (p = 0.046) and fewer unexpected family‐related problems (p = 0.045). They did not differ on depression, feelings about donation or family relationship quality. The findings suggest that the intervention merits testing in a larger, multisite trial. A single‐site clinical trial provides promising early evidence that a brief intervention offered to living kidney donors and living liver donors before surgery can prevent postdonation psychological distress, somatic complaints and donation‐related family problems.